2020
DOI: 10.1002/cmdc.201900642
|View full text |Cite
|
Sign up to set email alerts
|

An Atomistic Understanding of Allosteric Inhibition of Glutamate Racemase: a Dampening of Native Activation Dynamics

Abstract: Glutamate racemases (GR) are members of the family of bacterial enzymes known as cofactor‐independent racemases and epimerases and catalyze the stereoinversion of glutamate. D‐amino acids are universally important for the proper construction of viable bacterial cell walls, and thus have been repeatedly validated as attractive targets for novel antimicrobial drug design. Significant aspects of the mechanism of this challenging stereoinversion remain unknown. The current study employs a combination of MD and QM/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Exceptions to this strategy are seen with methylmalonyl-CoA epimerase 90 and mandelate racemase, 91,92 where the carboxylate group is ligated to the active site Co 2+ or Mg 2+ ion which acts as a Lewis acid and diminishes the pK a of the C a -H. 21 Typically the carboxylate group is also held within a hydrogen-bonding network with active-site residues. 5 Some racemase/epimerase substrates also contain further destabilising groups, such as ammonium groups (amino-acid racemases/epimerases), 18,20 amide carbonyl groups (N-succinylamino acid racemases, dipeptide epimerases and other enolase family enzymes 18,49 ) and OH (mandelate racemase, 18,91 various sugar epimerases 18 ).…”
Section: Racemisation and Epimerisation Reactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Exceptions to this strategy are seen with methylmalonyl-CoA epimerase 90 and mandelate racemase, 91,92 where the carboxylate group is ligated to the active site Co 2+ or Mg 2+ ion which acts as a Lewis acid and diminishes the pK a of the C a -H. 21 Typically the carboxylate group is also held within a hydrogen-bonding network with active-site residues. 5 Some racemase/epimerase substrates also contain further destabilising groups, such as ammonium groups (amino-acid racemases/epimerases), 18,20 amide carbonyl groups (N-succinylamino acid racemases, dipeptide epimerases and other enolase family enzymes 18,49 ) and OH (mandelate racemase, 18,91 various sugar epimerases 18 ).…”
Section: Racemisation and Epimerisation Reactionsmentioning
confidence: 99%
“…20,94,97,98 In some enzymes (e.g. glutamate racemase 21 ), this conformational change triggers a change in the conformation of the deprotonating activesite base as part of the pre-activation step which results in protonation of the substrate carboxylate group. It has also been suggested that conformational changes by 'capping domains', which result in the closed form of the racemase, activate the enzyme for catalysis, are important, e.g.…”
Section: Racemisation and Epimerisation Reactionsmentioning
confidence: 99%
See 3 more Smart Citations